Synthesis and antiviral evaluation of novel open-chain analogues of neplanocin A - Hong, JH; Kim, SY; Oh, CH; Yoo, KH; Cho, JH (TAYLOR & FRANCIS INC, 2006)
Novel acyclic nucleoside analogues were designed and synthesized as open-chain analogues of neplanocin A. The coupling of the allylic bromide with purine bases using cesium carbonate afforded a series of novel acyclic nucleosides. The synthesized compounds Ia-II were evaluated for their antiviral activity against various viruses such as HIV, HSV-1, HSV-2 and ECMV.
Keywords: ACYCLIC NUCLEOSIDES